2015
DOI: 10.1051/0004-6361/201424235
|View full text |Cite
|
Sign up to set email alerts
|

Lower mass normalization of the stellar initial mass function for dense massive early-type galaxies atz~ 1.4

Abstract: Aims. This paper aims at understanding whether the normalization of the stellar initial mass function (IMF) of massive galaxies varies with cosmic time and/or with mean stellar mass density Σ = M /(2πR 2 e ). Methods. We have tackled this question by taking advantage of a spectroscopic sample of 18 dense (Σ > 2500 M pc −2 ) massive early-type galaxies (ETGs) that we collected at 1.2 < ∼ z < ∼ 1.6. Each galaxy in the sample was selected in order to have available: i) a high-resolution deep HST-F160W image to vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 84 publications
4
4
0
Order By: Relevance
“…9. We note that the variation holds both for low-density and highdensity galaxies, in agreement with what previously found by Gargiulo et al (2015) for field spheroids at high redshift. For comparison, the M dyn /M * -σ relation of a sample of local spheroids extracted from the SPIDER sample (gray symbols; La Barbera et al 2010a) is also shown.…”
Section: The Formation Redshift Of Cluster Spheroidssupporting
confidence: 92%
See 2 more Smart Citations
“…9. We note that the variation holds both for low-density and highdensity galaxies, in agreement with what previously found by Gargiulo et al (2015) for field spheroids at high redshift. For comparison, the M dyn /M * -σ relation of a sample of local spheroids extracted from the SPIDER sample (gray symbols; La Barbera et al 2010a) is also shown.…”
Section: The Formation Redshift Of Cluster Spheroidssupporting
confidence: 92%
“…We notice that the relation between M dyn and M * dyn , as well the trend of M * dyn /M * -σ, i.e. the variation of IMF on σ and its possible evolution is out of the scope of the present work and it is treated in detail in other papers (e.g., Cappellari et al 2012Cappellari et al , 2013Tortora et al 2013;Ferreras et al 2013;Gargiulo et al 2015;La Barbera et al 2015;Lyubenova et al 2016, and references therein).…”
Section: The Formation Redshift Of Cluster Spheroidsmentioning
confidence: 91%
See 1 more Smart Citation
“…Comparing dynamical to simple stellar population (SSP) masses, Shetty & Cappellari (2014 find a Salpeter IMF, rather than the "universal" Chabrier, for their sample of massive (>10 11 M e ) ETGs atz 0.8. For a sample of ETGs atz 1.4 with both dynamical and photometric mass estimates, Gargiulo et al (2015a) report an IMF-σ relation consistent with the trends observed atz 0. They further posit that the IMF of dense (>2500 M e pc −2 ) ETGs is independent of redshift over the past ∼9 Gyr.…”
Section: Introductionsupporting
confidence: 68%
“…Based on studies of ETG populations atz 1 andz 1.4, observations beyond the local universe are beginning to suggest that the IMF-σ relation remains roughly constant over the past 8Gyr (Martín-Navarro et al 2015b;Gargiulo et al 2015a). Contrary to these studies, Sonnenfeld et al (2015) find that the overall log(a IMF ) at fixed velocity dispersion decreases from thez 0 value out toz 0.8.…”
Section: Implications For Imf Observationsmentioning
confidence: 94%